Case report: Bilateral spinal neurofibromatosis - Baradaran Bagheri, Ali; Aghajanian, Sepehr; Taghi Doulabi, Aliasghar; Chavoshi-Nejad, Mehdi; Sorouredin Abadi, Somayeh (Frontiers in Neurology, 2022)
Background Spinal neurofibromatosis (SNF) is a rare form of Neurofibromatosis in which neurofibromas exist bilaterally throughout all spinal roots. Despite previous attempts made to characterize and classify the disease as a separate clinical form of the disease, the low incidence rate of the disease and scarcity of previous reports calls for further studies and reports to elaborate this clinical entity. Case presentation The patient in this report was a 36-year-old man presenting with lower limb weakness, unsteady gait, and paresthesia. The patient presented with multiple large cutaneous café-eu-lait spots, cutaneous neurofibromas, and recurrent large neurocutaneous neurofibroma of right facial nerve. Magnetic resonance imaging (MRI) of spine revealed bilateral spinal neurofibromas in all spinal cord roots. MRI study of head revealed no abnormalities in the brain and optic tract. The patient fulfilled both NIH criteria as well as revised criteria for NF1. Despite total spinal cord involvement, surgical intervention was withheld from the patient due to high propensity of recurrence as seen with previous attempts in removing peripheral neurofibromas, slow progression of symptoms, and lack of significant pain and impairment. Conclusions SNF is often described as a form of disease with restricted presentation of classical NF1 stigmata other than spinal tumors. The case presented here however, presented with several cutaneous neurofibromas and café-au-lait spots. Considering the positive outcome of surgical intervention in a few other reports, the decision to surgically intervene should be left to the clinical judgement of the participating surgeon, patient preference and socioeconomic background in a case-by-case manner.